2022
DOI: 10.1155/2022/8233840
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Pyroptosis-Related Signature for Prognosis Prediction and Immune Microenvironment Infiltration in Prostate Cancer

Abstract: This study was aimed at constructing a pyroptosis-related signature for prostate cancer (PCa) and elucidating the prognosis and immune landscape and the sensitivity of immune checkpoint blockade (ICB) therapy in signature-define subgroups of PCa. We identified 22 differentially expressed pyroptosis-related genes in PCa from The Cancer Genome Atlas (TCGA) database. The pyroptosis-related genes could divide PCa patients into two clusters with differences in survival. Seven genes were determined to construct a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In addition, the 1-, 3-, and 5-year AUC values in the test set also had desirable results. Our risk model had excellent predictive power compared to other published pyroptosis-based prognostic models in PCa ( 45 , 46 ). Different from the direct use of Lasso to build a prognostic model of eight pyroptosis-related genes in the study of Wang et al.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the 1-, 3-, and 5-year AUC values in the test set also had desirable results. Our risk model had excellent predictive power compared to other published pyroptosis-based prognostic models in PCa ( 45 , 46 ). Different from the direct use of Lasso to build a prognostic model of eight pyroptosis-related genes in the study of Wang et al.…”
Section: Discussionmentioning
confidence: 68%
“…A comprehensive and in-depth understanding of the TME by pyroptosis in PCa is needed. Zhang et al identified several pyroptosis-related genes that may impact the prognosis of PCa patients by altering the TME ( 50 ), but the precise mechanism has yet to be uncovered. These findings indicate that pyroptosis is closely related to the development of PCa.…”
Section: Pyroptosis In Prostate Diseasementioning
confidence: 99%
“…It can effectively stratify the risk of PCa patients into subgroups that are more suitable for immunotherapy and potentially serve as indicators of response to immunotherapy for PCa. [ 106 ] Li et al, by building a prognostic model with 5 PRGs, validated that the risk scores of these 5 PRGs were independent factors for relapse in PCa patients and were found to be related to the immune microenvironment. [ 105 ] Fu et al constructed 2 different pyroptosis patterns based on extensive RNA-seq and scRNA-seq data from PCa patients.…”
Section: Role Of Pyroptosis In Pcamentioning
confidence: 99%